Hidrogeneoftalato de potássio como molécula modelo para estudos de adsorção sobre TiO2 - Valente, José Pedro Serra [UNESP]; Bozano, Dorotéia de Fátima [UNESP]; Costa Jr., Ciniro [UNESP]; Florentino, Ariovaldo de Oliveira [UNESP] (My University, 2002)
The aim of the work was to use the potassium hydrogenphthalate as molecule model for adsorption studies on TiO2. The results of adsorption of the hydrogenphthalate on TiO2 were fitted to the models proposed by Langmuir and Freundlich, but the model of Freundlich described better the phenomenon. The adsorption was a function of the temperature and the capacity of adsorption increased from 2,4 to 4,5 mg.g-1 when the temperature was increased from 20°C to 30°C.
Potassium hydrogenphthalate as molecule model for adsorption studies on TiO2
Keywords: Adsorption; Freundlich Isotherms; Langmuir Isotherms; Potassium hidrogenphthalate; TiO2